Intergenerational relations, demography and economy in relation with pensions - Fernández Cordón, Juan Antonio (Cuadernos de Relaciones Laborales, 2015)
Support of dependent persons relies on social organization, always based on intergenerational reciprocity. No pension system may be conceived without a reference to this social frame. Dependency needs can never be fulfilled by the individual him or herself and always involve a three generations scheme. Recent reforms of the “pay-as-you-go” public pension systems are progressively introducing in them the rationale of funded pension systems, where the saving-pensioner bears all risks. This leads to a narrow accountant view on pensions that prevents exploring for innovative solutions to the demographic, social and economic problems faced by the more developed countries. Most of the catastrophic predictions of the pretended unaffordable future cost of pensions may be proven wrong if all societal variables are allowed to change, especially those affecting income distribution. Demography is far from being the main, let alone the only, factor to determine the future of pensions. The economy plays a leading role thru job creation, increase in labour productivity and reduction of inequalities. Demographic ageing is a social challenge that we are in a position to overcome.
Keywords: ageing; pensions; income distribution